Characterization and fungicide sensitivity of Colletotrichum godetiae causing sweet cherry fruit anthracnose in Guizhou, China - Peng, Keqin; Pan, Yintao; Tan, Tingjun; Zeng, Xiangyu; Lin, Meiling; Jiang, Shuang; Zhao, Zhibo; Tian, Fenghua; Zhao, Xiaosheng (Frontiers in Microbiology, 2022)
Sweet cherry is an important fruit crop with high economic and ornamental value in China. However, cherry fruit anthracnose, caused by Colletotrichum species, greatly impacts cherry yield and quality. Here, we surveyed cherry anthracnose in Guizhou, China from 2019-2020. Necrotic sweet cherry fruits were collected from different areas in Guizhou and examined. A total of 116 Colletotrichum strains were isolated from these symptomatic fruits. Based on the morphological characteristics of the isolates and phylogenetic analyses of concatenate internal transcribed spacer (ITS) region and ACT, CHS-1, GAPDH , TUB2 and HIS3 genes, the pathogen responsible for causing sweet cherry anthracnose was identified as Colletotrichum godetiae. Pathogenicity tests were conducted by inoculating healthy sweet cherry fruits with spore suspensions of the fungal pathogen, and Koch’s postulates were confirmed by pathogen re-isolation and identification. The Q-1 isolate showed different sensitivities to 13 fungicides, exhibiting seven different modes of action, and its EC50 values ranged from 0.04 to 91.26 ug mL-1. According that, the sensitivity of 20 isolates from different samples to ten fungicides with better perfomance , were measured. The results showed that 6 of the 10 fungicides (difenoconazole, propiconazole, prochloraz-manganese, pyraclostrobine , trifloxystrobin-tebuconazole and difenoconazole-azoxystrobin) all showed higher sensitive to the 20 C. godetiae isolates, and no resistance groups appeared. Its EC50 values ranged from 0.013 to 1.563 ug mL-1.